SLC25A3 exports mitochondrial copper to metalate cytochrome c oxidase and prevent cuproptosis - Mohammad Zulkifli; Ifrah Farid; Laura E. Oldfather; Vinit C. Shanbhag; Scot C. Leary; Michael J. Petris; Paul A. Cobine; Vishal M. Gohil (Proceedings of the National Academy of Sciences, 2026)
Copper (Cu) is an essential cofactor for cytochrome c oxidase (CcO), a mitochondrial respiratory chain enzyme that is metalated in the intermembrane space (IMS) primarily using Cu derived from the mitochondrial matrix pool. While Cu import into the matrix depends on the inner membrane carrier SLC25A3, the route by which matrix Cu is exported to the IMS for insertion into CcO has remained a major, unresolved step in intramitochondrial Cu trafficking. Here, we leveraged our recent discovery that the Cu ionophore elesclomol (ES) releases Cu directly into the mitochondrial matrix to show that SLC25A3 is required for exporting Cu to the IMS for CcO metalation. Loss of SLC25A3 decreases mitochondrial Cu content and CcO activity as expected. Strikingly, bypassing the loss of SLC25A3 with ES-mediated Cu delivery to the matrix fails to restore CcO function; rather, it drives toxic Cu retention and triggers cuproptosis, revealing that SLC25A3-facilitated Cu export is the limiting determinant of CcO metalation. Heterologous expression in Lactococcus lactis confirms that SLC25A3 can mediate Cu export. These results suggest that SLC25A3 is the long-sought mitochondrial Cu exporter with a dual role in enabling CcO metalation and gating susceptibility to cuproptosis.